Students’ Responses to Adapted Online Tahsin Quran Learning during the COVID-19 Pandemic - Rifda Shabrina; Uwes Anis Chaeruman; Indina Tarjiah (TARBIYA: Journal of Education in Muslim Society, 2021)
AbstractTahsin Quran is a method of learning to read the Quran that strives to increase the reader's ability to adhere to the guidelines established (tajwid). In tahsin Quran learning, teachers must pay close attention to students' letter pronunciation in the Quran, ideally face-to-face or in sync. However, the COVID-19 pandemic has necessitated online learning, requiring some alterations to its application. The purpose of this study was to determine how students respond to online Quran learning conducted virtually in one of South Tangerang's Quran learning facilities. Students are given questionnaires about instructor competencies, the substance of learning materials, and the efficiency of tahsin online learning, which are reinforced by an interview with one of the teachers, an institution member, and students. The results indicated that, based on student answers, the institution's implementation of tahsin Quran online learning has been highly successful, with some notes and inputs to consider to improve the quality of Quran online learning in the future.AbstrakTahsin Al-Qur’an merupakan pembelajaran membaca Al-Qur’an yang bertujuan untuk memperbaiki bacaan Al-Qur’an agar sesuai dengan kaidah (tajwid) yang ditetapkan. Dalam pembelajaran tahsin Al-Qur’an, guru atau instruktur perlu memperhatikan ketepatan tiap siswanya dalam melafalkan huruf dalam Al-Qur’an sehingga pembelajaran idealnya dilakukan secara tatap muka atau sinkron. Namun pandemi COVID-19 mengharuskan pembelajaran dilaksanakan secara daring sehingga membutuhkan beberapa penyesuaian dalam pelaksanaannya. Penelitian ini bertujuan untuk meneliti bagaimana respon siswa pembelajaran tahsin Al-Qur’an online yang dilaksanakan secara virtual di salah satu lembaga pembelajaran Al-Qur’an di Tangerang Selatan. Kuesioner mengenai kemampuan guru, isi materi pembelajaran, dan efektifitas pembelajaran tahsin yang dilaksanakan secara online diberikan kepada siswa yang kemudian hasilnya dilengkapi dengan hasil wawancara kepada salah satu guru, pihak lembaga, dan siswa. Hasil penelitian menunjukkan bahwa berdasarkan respon siswa pembelajaran tahsin Al-Qur’an online yang dilaksanakan di lembaga tersebut telah berjalan sangat baik dengan beberapa catatan dan masukan yang perlu diperhatikan untuk peningkatan kualitas pembelajaran tahsin Al-Qur’an daring yang akan datang.How to Cite: Shabrina, R., Chaeruman, U. A., Tarjiah, I. (2021). Students’ Responses to Adapted Online Tahsin Quran Learning during the COVID-19 Pandemic. TARBIYA: Journal of Education in Muslim Society, 8(1), 57-65. doi:10.15408/tjems.v8i1.21715.